2003
DOI: 10.1126/science.1076807
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Roles of PHAP Proteins and Prothymosin-α in a Death Regulatory Pathway

Abstract: A small molecule, alpha-(trichloromethyl)-4-pyridineethanol (PETCM), was identified by high-throughput screening as an activator of caspase-3 in extracts of a panel of cancer cells. PETCM was used in combination with biochemical fractionation to identify a pathway that regulates mitochondria-initiated caspase activation. This pathway consists of tumor suppressor putative HLA-DR-associated proteins (PHAP) and oncoprotein prothymosin-alpha (ProT). PHAP proteins promoted caspase-9 activation after apoptosome form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
282
1
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(300 citation statements)
references
References 39 publications
5
282
1
11
Order By: Relevance
“…16 Wang Lab demonstrated that pp32 augments the activity of the apoptosome, leading to more caspase 9 activity ex vivo. 20 They did not obtain any in vivo data because of failure to knock down pp32 with RNAi. We succeeded in silencing pp32 expression in Jurkat cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Wang Lab demonstrated that pp32 augments the activity of the apoptosome, leading to more caspase 9 activity ex vivo. 20 They did not obtain any in vivo data because of failure to knock down pp32 with RNAi. We succeeded in silencing pp32 expression in Jurkat cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that pp32 induces caspase-9 activation to promote apoptosome formation in caspase-dependent apoptosis. 20 Jurkat cells with 3 days pp32 overexpression were treated with UV irradiation and incubated overnight. Cytosolic caspase activity was analyzed by degrading their specific fluorogenic substrates.…”
Section: Overexpression Of Pp32 Reduces Acetylation and Phosphorylatimentioning
confidence: 99%
“…Several studies have demonstrated ProTα's function in immune regulatory activity and potentiation of the immune system (Cordero et al, 1991;Oates et al, 1988). Recent studies documented that ProTα also played a regulatory role in apoptosis because of the significance of this process in development, cell turnover, and tumorigenesis (Emmanouilidou et al, 2013;Jiang et al, 2003;Qi et al, 2010;Tripathi et al, 2011). First identified from a cytokine-like activity, Tβs play significant roles in various physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hsp27 has been found to prevent Smac release from mitochondria in multiple myeloma cell lines and patient-derived cells, which could help to explain the resistance of these cancer cells to certain apoptotic stimuli. 72 Putative HLA-DR-associated protein-1 (PHAP1) and prothymosin-a (ProT) were identified as apoptosome regulators in a screen for small molecules that activate caspase-3 (reference Jiang et al 73 ). PHAP1 appears to facilitate caspase-9 activation after apoptosome formation, whereas ProT negatively regulates caspase-9 activation by inhibiting assembly of the apoptosome.…”
Section: Spinning the Roulette Wheel: Direct And Indirect Modulation mentioning
confidence: 99%